Production and Engine Performance Analysis of Karanja Biodiesel using Synthesized CaO Catalyst - Dewi, Harreh (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research focuses primarily on production of Karanja biodiesel using heterogeneous catalyst. CaO derived from Meretrix lyrata (M.lyrata) shell was an environmental friendly heterogeneous catalyst for sustainable biodiesel production. The CaO catalyst was synthesized from M.lyrata by calcination-hydration-dehydration technique. The catalytic performance of synthesized CaO was investigated in the yield product of Karanja methyl ester (KME) from crude Karanja oil (CKO). KME was produced through acid esterification using H2SO4 followed by transesterification in presence of CaO in a two-step reaction process of CKO and methanol. The M.lyrata shells were calcined at 800 ℃ and the catalyst samples were characterized using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), Particle Size Analyzers (PSA), and Brunauer-Emmett-Teller (BET) Surface Area Analysis and Barrett-Joyner-Halenda (BJH) Pore Size and Volume Analysis techniques. A maximum fatty acid methyl ester (FAME) conversion of 97.3% was obtained at optimum parameter at methanol to oil ratio of 12:1, catalyst concentration of 2 wt%, reaction temperature of 58 ℃ and reaction time of 2 hours. Incomparative study with the commercial CaO, the M.lyrata synthesized CaO catalyst showed a higher catalytic activity. The catalyst reusability experiments ascertain reusability of CaO up to four reuse cycles had shown good efficiency. The economic comparative study confirms that CaO derived from M.lyrata can be used as an alternative and feasible catalyst for the biodiesel production. The characterization of KME shows that the produced biodiesel had a potential to be used as a blend with diesel. The KME fuel properties comply according to EN 14214 biodiesel fuel standards. The physiochemical properties of the CKO produced revealed that it conforms with EN14214 standards for brake power (BP), brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) as they are all noted be optimal at B15. Hence, this research recommends use of B15 biodiesel blends.